FAKTOR YANG BERHUBUNGAN DENGAN ANAK BALITA STUNTING PADA KELUARGA NELAYAN - Ahmad Rizal; Mariatul Haya (Poltekkes Kemenkes Kalimantan Timur, 2020)
The problem of malnutrition is caused by the low comsumption of caloriesand proteins contained in daily food, andcaused by certain deseases. Food comsumption effects Nutritional status. Good Nutritonal status or optimal nutritional status. Children under five in poor families are prone to malnutrion due to their diet and quantity that do not fulfill their nutritional needs. Stunting is a long-lasting deficiency that can even occur since a child is still in the womb. Stunting is an indicator of chronic malnutrition that describes a long history of childhood nutrition. The purpose of this study was to analyze factor related to stunting children in fishing families in the work area of teluk segara subdistrict, Bengkulu city in 2018. This study uses quantitative with cross sectional design, sampling tecniques with purposive sampling data analysis by univariate and bivariate by correlation test. The result showed that there was a significant relationship between energy intake and stunting toddlers. This is indicated by P value 0.031 (<0.05) and there is a significant relationship between protein intake and stunting toddlers with P value 0.048 (<0.05)and there is no relationship between birth weight, initiation of early breastfeeding and exclusive breastfeeding with toddlers stunting family of fisherman. Based on the result of the pearson correlation test the result of the relationships were meaningful and showed the value of r produced – 0.395 and – 0.364 with a negative pattern. This shows a relationship with a low correlation. So that the results of this study can be used as information for puskesmas for program planning in overcoming stunting problems.